2016
DOI: 10.1007/s10290-016-0246-0
|View full text |Cite
|
Sign up to set email alerts
|

Night lights and regional GDP

Abstract: Standard-Nutzungsbedingungen:Die Dokumente auf EconStor dürfen zu eigenen wissenschaftlichen Zwecken und zum Privatgebrauch gespeichert und kopiert werden.Sie dürfen die Dokumente nicht für öffentliche oder kommerzielle Zwecke vervielfältigen, öffentlich ausstellen, öffentlich zugänglich machen, vertreiben oder anderweitig nutzen.Sofern die Verfasser die Dokumente unter Open-Content-Lizenzen (insbesondere CC-Lizenzen) zur Verfügung gestellt haben sollten, gelten abweichend von diesen Nutzungsbedingungen die in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
61
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 82 publications
(63 citation statements)
references
References 11 publications
(15 reference statements)
2
61
0
Order By: Relevance
“…Given the fact that some studies have looked into predicting GDP with nighttime lights (Chen and Nordhaus, 2010;Elvidge et al, 2007;Sutton et al, 2007), our findings suggest that caution must be taken when interpreting monthly nighttime lights as a proxy for economic activity, because there are additional factors which drive the emissions night lights besides economic activity. Indeed, Bickenbach et al (2013) concluded that night lights data may be poor proxies for regional GDP. Due to the phenological cycle of vegetation and seasonal changes in snow cover, variations which are not related to the emission of nighttime lights can be introduced into nighttime light time series.…”
Section: Discussionmentioning
confidence: 99%
“…Given the fact that some studies have looked into predicting GDP with nighttime lights (Chen and Nordhaus, 2010;Elvidge et al, 2007;Sutton et al, 2007), our findings suggest that caution must be taken when interpreting monthly nighttime lights as a proxy for economic activity, because there are additional factors which drive the emissions night lights besides economic activity. Indeed, Bickenbach et al (2013) concluded that night lights data may be poor proxies for regional GDP. Due to the phenological cycle of vegetation and seasonal changes in snow cover, variations which are not related to the emission of nighttime lights can be introduced into nighttime light time series.…”
Section: Discussionmentioning
confidence: 99%
“…To the best of our knowledge, we are the first to introduce G rate to extend the current disease measurement systems in modern epidemiology. The size of geographic area has been considered as an important measurement component in other fields, including environmental science ( Levin and Kerster, 1969 , Nambinina et al, 2016 ), demography ( Langford and Unwin, 1994 , Pearl and Parker, 1922 ), and economics ( Bickenbach et al, 2016 , Gallup et al, 1999 ). However, no reported studies have ever factored this component into any formal rate indicators in epidemiology.…”
Section: Discussionmentioning
confidence: 99%
“…Panel data estimate that condition on state and year fixed effects indicate that a 1 per cent increase in night lights is associated with a 0.12 per cent increase in GDP (see Table A.3). Using Indian district level GDP data that are available for a few recent years, Bickenbach et al (2013) estimate an elasticity of 0.107. Using global data, Henderson et al (2012) estimate an elasticity of about 0.3.…”
Section: Night Lights Datamentioning
confidence: 99%